Design Principles for Pluripotent Stem Cell-Derived Organoid Engineering - Teresa P. Silva; João P. Cotovio; Evguenia Bekman; Maria Carmo-Fonseca; Joaquim M. S. Cabral; Tiago G. Fernandes (Stem Cells International)
Human morphogenesis is a complex process involving distinct microenvironmental and physical signals that are manipulated in space and time to give rise to complex tissues and organs. Advances in pluripotent stem cell (PSC) technology have promoted the in vitro recreation of processes involved in human morphogenesis. The development of organoids from human PSCs represents one reliable source for modeling a large spectrum of human disorders, as well as a promising approach for drug screening and toxicological tests. Based on the “self-organization” capacity of stem cells, different PSC-derived organoids have been created; however, considerable differences between in vitro-generated PSC-derived organoids and their in vivo counterparts have been reported. Advances in the bioengineering field have allowed the manipulation of different components, including cellular and noncellular factors, to better mimic the in vivo microenvironment. In this review, we focus on different examples of bioengineering approaches used to promote the self-organization of stem cells, including assembly, patterning, and morphogenesis in vitro, contributing to tissue-like structure formation.